Family Disadvantage and the Gender Gap in Behavioral and Educational Outcomes - David H. Autor; David N. Figlio; Krzysztof Karbownik; Jeffrey Roth; Melanie Wasserman (Center for Economic Studies and ifo Institute (CESifo), 2016)
Using birth certificates matched to schooling records for Florida children born 1992 – 2002, we assess whether family disadvantage disproportionately impedes the pre-market development of boys. We find that, relative to their sisters, boys born to disadvantaged families have higher rates of disciplinary problems, lower achievement scores, and fewer high-school completions. Evidence supports that this is a causal effect of the post-natal environment; family disadvantage is unrelated to the gender gap in neonatal health. We conclude that the gender gap among black children is larger than among white children in substantial part because black children are raised in more disadvantaged families.
Keywords: J12; J13; J16; I24; 330; gender gap; family structure; education and inequality; early skills development